Decolonial Museology: the Points of Memory and the insurgency of making museums: Tese de Doutoramento (Cadernos de Sociomuseologia, 2018)
This study presents the Memory Points Program trajectory from 2008, the year of its launch, to the present day. The purpose of this thesis is to analyze the documents coming from the Technical Cooperation between the Brazilian Institute of Museums, the Ministry of Culture, the Organization of Ibero-American States: for education, science and culture and the Ministry of Justice, with the aim of to encourage museum processes in popular communities located in twelve Brazilian capitals considered by the National Program for Security with Citizenship - Pronasci, violent. With a view to discussing the accumulations, difficulties and potency of this Program for the field of museums and museology, we propose to analyze aspects related to the political, poetic and pedagogical dimension of Memory Points, with emphasis on the assumptions of colonialists, especially those as a result of the decolonial studies of the Modernity / Coloniality Group. Inspired by the ideas of confrontation highlighted by the indignation of living in a colonizing, macho, patriarchal, homophobic and prejudiced society, we consider that it is possible, through critical and participatory museum processes and actions, to confront the colonialities of being, knowledge and power produced with a view to perpetuating situations of neglect, subalternity and invisibility of the subjects and their territories. In our understanding, the Points of Memory Program focusing on the role of museums and museology in society means advances in the consolidation of the field of Social Museology in Brazil, the result of a National Museum Policy that is strengthened towards Social Policies dedicated to guaranteeing the Right to Memory and the dignity of historically and socially and culturally excluded groups and communities. We understand this program as an insurgent and decolonizing action of museological thought and practice. Keywords: Memory Points; Museology; Social Museology; Studies of Decolonial; Decolonial Museology and Public Policy.